Distributed swarm system with hybrid-flocking control for small fixed-wing UAVs: Algorithms and flight experiments - Song, Yeongho; Lim, Seunghan; Myung, Hyunsam; Lee, Hokeun; Jeong, Junho; Lim, Heungsik; Oh, Hyondong (Expert systems with applications, 2023)
This paper presents a distributed swarm system for small fixed-wing unmanned aerial vehicles (UAVs). In particular, to perform various missions with multiple UAVs that are densely gathered and collision free, a hybrid-flocking control algorithm is synthesized by using three types of control protocols: vector field guidance (for path following/loitering), augmented Cucker–Smale (ACS) model (for collective flocking behavior), and potential field (for collision avoidance). In particular, to address the issue of conflicts between different control protocols, the adaptive ACS model is proposed and the optimization problem is formulated to determine the suitable mixing weights of control protocols. We also design the transition of multiple operation modes and communication architecture for the swarm system. The system is evaluated using the proposed hybrid-flocking control algorithm by proof-of-concept real flight experiments using 18 small fixed-wing UAVs as well as extensive numerical simulations. Flight experiments are successfully performed for multiple consecutive tasks including the individual task, circular path loitering and elliptical path loitering while avoiding collisions among UAVs. •The distributed small fixed-wing UAV swarm system is designed.•The hybrid-flocking control algorithm is proposed by combining three control protocols.•The optimal mixing weight improves the mission performance.•Numerical simulations and flight experiments validate the hybrid-flocking algorithm.